A systematic review and meta-analysis of medium-chain triglycerides effects on acute satiety and food intake. Issue 4 (21st February 2021) - Maher, Tyler; Clegg, Miriam E.
Abstract: Research has indicated that consuming medium-chain triglycerides (MCT) may be more satiating than consuming long-chain triglycerides (LCT) potentially causing a reduction in energy intake. However not all studies have demonstrated this acute reduction in energy intake and it has yet to be systematically reviewed. Our main objective was to examine how ingestion of MCT influences energy intake, subjective appetite ratings and appetite-related hormones compared to LCT. Web of Science, MEDLINE, CINHAL, and Embase were searched for publications comparing the effect of MCT on appetite (commonly hunger, fullness, desire to eat, and prospective food consumption), appetite-related hormones (pancreatic polypeptide (PP), gastric inhibitory polypeptide (GIP), peptide YY (PYY), glucagon-like peptide-1 (GLP-1), neurotensin, leptin, total ghrelin and active ghrelin) and energy intake to LCT. A random-effects meta-analysis was conducted on studies which examined energy intake. Seventeen studies (291 participants) were included in the systematic review, of which 11 were included in the energy intake meta-analysis. Synthesis of combined data showed evidence of a statistically significant moderate decrease in ad libitum energy intake after both acute and chronic ingestion of MCT compared to LCT when assessed under laboratory conditions (mean effect size: −0.444, 95% CI −0.808, −0.080, p  < 0.017), despite little evidence of any effect of MCT on subjective appetite ratings or circulating hormones. The current evidence supports the notion that MCT decreases subsequent energy intake, but does not appear to affect appetite. Further research is warranted to elucidate the mechanisms by which MCT reduce energy intake.